The relationship between audit quality and earnings management;Evidence from China - Liu, Yaotian (2019)
This study takes the data of China's main board manufacturing companies from 2015 to 2017 as a sample, uses the modified Johns (1995) model to calculate the enterprise's accrual earnings management level, and uses Roychowdhury's (2006) method to calculate the company's real earnings management level. A comprehensive indicator reflecting the quality of the external audit is constructed combining the size of the accounting firm, the auditor industry expertise and the type of audit opinion. At the same time, the paper introduces indicators such as company size, asset-liability ratio, and total asset net interest rate as control variables. Based on the existing research results, a suitable multivariate regression model is established. The study found that audit quality can have a significant effect on the company's accrued earnings management activities, but the effect on real earnings management is not obvious. In addition, companies are more effective in implementing real earnings management activities than accrual earnings management.